2017
DOI: 10.3892/ijo.2017.3974
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity in FANCG, FANCF and BRIP1 from head and neck squamous cell carcinoma of the oral cavity

Abstract: Recent advances have been made in the understanding of Fanconi anemia (FA), a hereditary disease that increases the risk for head and neck squamous cell carcinomas (HNSCC) by 500- to 700-fold. FA patients harbour germline mutations in genes of cellular DNA repair pathways that are assumed to facilitate the accumulation of mutations during HNSCC development. Mutations in these FA genes may also contribute to HNSCC in general. In the present study, we analysed three FA genes; FANCF, FANCG and BRIP1, that are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…Several genomic alterations have been identified in OL, including single nucleotide variations and mutation hotspots in genes related to the cell cycle and cancer regulatory pathways, such as TP53, Ki-67, and NOTCH1 (Zhang et al, 2017;Ding et al, 2018;Yagyuu et al, 2017;Gissi et al, 2015). Loss of heterozygosity and changes in DNA methylation are also significantly associated with clinical outcomes in OL patients (Tsao et al, 2009;Zhou et al, 2011;Zhang et al, 2012;Türke et al, 2017). However, the frequencies of these mutations and altered biomarkers are low, and only a small number of OL cases harbor these genetic alterations (Mello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several genomic alterations have been identified in OL, including single nucleotide variations and mutation hotspots in genes related to the cell cycle and cancer regulatory pathways, such as TP53, Ki-67, and NOTCH1 (Zhang et al, 2017;Ding et al, 2018;Yagyuu et al, 2017;Gissi et al, 2015). Loss of heterozygosity and changes in DNA methylation are also significantly associated with clinical outcomes in OL patients (Tsao et al, 2009;Zhou et al, 2011;Zhang et al, 2012;Türke et al, 2017). However, the frequencies of these mutations and altered biomarkers are low, and only a small number of OL cases harbor these genetic alterations (Mello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…14 BRIP1 directly interacts with the C terminus domain of breast cancer 1 (BRCA1), thus playing a crucial role in DNA damage repair. 15 Previous studies have suggested that hyperglycemic condition interferes the genetic stability and impairs the functionality of DNA repair through down-regulating DNA repair genes, thus inducing carcinogenesis. 16 However, in the OSCC cells treated with high glucose, BRIP1 showed an overexpression in contradiction with IHC result, indicating that the decreased expression of BRIP1 in OSCC patients with T2DM might not be correlated with hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…BRIP1, as an anti‐oncogenic factor, has been observed to be downregulated in various cancers including head and neck squamous carcinoma 14 . BRIP1 directly interacts with the C terminus domain of breast cancer 1 (BRCA1), thus playing a crucial role in DNA damage repair 15 . Previous studies have suggested that hyperglycemic condition interferes the genetic stability and impairs the functionality of DNA repair through down‐regulating DNA repair genes, thus inducing carcinogenesis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Fanconi anaemia (FA) results from chromosomal instability due to biallelic mutations in one of the 17 known FA genes (FANCA to FANCS), inherited in an autosomal recessive or X-linked recessive pattern [17]. Germline mutations in genes of cellular DNA repair pathways are assumed to facilitate accumulation of mutations during HNSCC development [18]. Mutations in these FA genes may also contribute to the development of HNSCC in general [18].…”
Section: Inherited Hnsccmentioning
confidence: 99%